(3Gdbhd GdKGHJ aj GdWHs - (3eMeO Hf CMeO Hf YHO Gdedc, CHh YHO Gddg GdparTJGdj , bGVj aGS,J (B777 (3g` s
(3ChdgG (B:s
(3Gdbhd ai GdHQ (B: (3GdHQ QWH MGQ HGYJOGd , hgh CZPi GdMHhH edGAeg dHOf GdEfSGf CaVdg eG cGf s
(3BNQgG (B:s
(3aGddg SHMGfg jHbi HQcJce , hjOje Hefg YRJce hGdSdGe s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B225 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B286s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B184 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs